The Economic Impact of Halal Tourism Development on Local Communities - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research examines the economic dynamics of halal tourism development in Setanggor Village, a traditional craft village in Lombok, Indonesia, focusing on the interrelationship between cultural preservation and sustainable economic growth. Digital ethnographic methodology facilitates comprehensive analysis by systematically observing online interactions, digital footprints, and virtual community engagements across social media platforms, e-commerce activities, and digital marketing strategies of Setanggor's artisanal enterprises. Data collection encompasses news articles, and TripAdvisor reviews specific to Setanggor Village, processed through Atlas.ti software for rigorous content categorization and thematic analysis. Pattern identification and cross-source validation enhance analytical depth, ensuring methodological coherence in deriving robust conclusions. The findings reveal significant correlations between community cooperative structures, artisan empowerment, and equitable distribution of economic benefits within Setanggor's traditional weaving industry. Market expansion through halal-certified products demonstrates the substantial potential for income generation, while Setanggor's traditional weaving practices exemplify the successful integration of cultural heritage with contemporary market demands. However, the research identifies critical challenges in maintaining an equilibrium between commercialization pressures and cultural authenticity. Implementing strategic policy frameworks and fair trade mechanisms emerges as essential for fostering sustainable economic development while preserving traditional craftsmanship. This investigation contributes to the academic discourse by establishing innovative approaches for evaluating tourism-driven economic impacts within traditional craft villages, offering valuable insights for policymakers and stakeholders in developing sustainable halal tourism initiatives that benefit local artisanal communities in Setanggor and similar cultural destinations.